In-situ X-ray diffraction analysis of the recrystallization process in Cu2ZnSnS4nanoparticles synthesised by hot-injection - Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Azimi, Seyed Hamed; Hou, Yi; Peukert, Wolfgang; Brabec, Christoph; Hock, Rainer (Thin Solid Films, 2015)
Kesterite CuZnSnS(CZTS) is a promising material for thin film solar cell applications. The biggest advantages of this compound lie in the abundance and non-toxicity of the contained elements. Low temperature hot injection synthesis can provide an economic way to produce CZTS nanoparticles for application in solution processed solar cells. Powder X-ray diffraction (PXRD) measurements on the as-synthesised particles suggest that the crystal structure is cubic and can be best described as sphalerite-like. This means that the cations in the CZTS are statistically distributed on the cation sites of the crystal lattice rather than well-ordered like in the tetragonal kesterite structure. An in-situ PXRD measurement while annealing the particles up to 550 °C revealed a recrystallization process that transforms the structure from cubic to tetragonal meaning an ordering of the cations.
Keywords: Copper zinc tin sulphide; Cubic phase; Hot-injection synthesis; In-situ; Phase transition; Tetragonal phase; X-ray diffraction